TINGKAT KEPUASAN PENERIMA BANTUAN RUMAH DHUAFA DI PROVINSI ACEH (STUDY KASUS: KABUPATEN ACEH UTARA) - Fani Saputra; Mochammad Afifuddin; Abdul Munir (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Aceh province, especially in North Aceh Regency, there are still many poor people who do not have a house as a means of decent residence to be occupied. Therefore, In 2016 the Government of North Aceh allocates about 120 units of houses dedicated to the Help Home. The house which is sourced from APBA fund is a development activity of simple healthy house of III area which has been completed and some have been given to the people who are entitled to receive. This study aims to determine the condition of existing houses and the level of home receipts satisfaction that is destined for the Help Home in North Aceh district in 2016. The methodology used mix methods between qualitative and quantitative while the number of samples used as many as 55 respondents from the population of 120 units. The existing condition of the house that became the object of research is a house type 36 with 2 bedroom units with an area of 3,80 x 2,50 m; family room 4,85 x 2,50 m; bathroom 1,40 x 1,75 m; and a front porch with a size of 2,50 x 1,50 m. The level of satisfaction is analyzed based on frequency index analysis. The result shows that the cause of dissatisfaction of the society to the relief house are: house size with the value of frequency index (FI) 0,32; the amount and space of the house with the value of FI 0,33; clean water network (PDAM or drilling well) with value of FI 0,34; access to health facilities (puskesmas / RS) with an FI value of 0,34; the state of the door / window (when opened and closed again) with a value of FI 0,35; access reach security post (security / polsek / polres) with value FI 0,36; access to public transport with an FI value of 0,37; and quality and condition of bathroom and septitank with value 0,38. From the results of the study it can be concluded that the beneficiary community of Help Home is less satisfied with the assistance.